In-plane seismic behaviour of retrofitted masonry walls subjected to subsidence-induced damage. (15th November 2020) - Drougkas, Anastasios; Licciardello, Lucia; Rots, Jan G.; Esposito, Rita
Highlights: Bed joint reinforced repointing is investigated experimentally & numerically. In-plane stiffness & capacity are increased by bed joint reinforced repointing. Bed joint reinforced repointing causes out-of-plane effects during in-plane loading. Abstract: The province of Groningen in the Netherlands is experiencing the continuous impact of gas extraction in the form of induced seismicity. Due to the absence of naturally occurring seismicity in the region, the historic building stock of Groningen was constructed without empirical design features typically encountered in naturally seismic regions. Further, gas extraction, in combination with soft topsoil, is responsible for substantial amounts of ground subsidence. This subsidence may compromise the capacity of existing structures to bear seismic loading. Historic masonry structures, particularly those lacking traditional earthquake-resistant features, are vulnerable to seismic loads. Further, their substantial weight, in-plane stiffness, low tensile strength and brittleness renders them vulnerable to settlement-induced damage. Given the cultural significance of architectural heritage, the performance of historic buildings in the Damage Limitation (DL) state is a matter of importance. Additionally, due to the incorporation of both vernacular and monumental architectural heritage buildings in the urban setting, their performance in the Near Collapse (NC) state is as important as that of ordinary building structures. Therefore, methods and techniques for enhancing the behaviour of historic buildings in both States need to be devised and evaluated. This paper focuses on the application and assessment of a retrofitting technique commonly used for damage prevention and repair in unreinforced masonry structures in the Netherlands, namely bed joint reinforced repointing. The technique consists in the embedment of stainless-steel bars in continuous bed joints, as well as their dry placement across cracks in the masonry. The technique is applied on a masonry wall tested under quasi-static cyclic in-plane shear loading for the evaluation of its performance not only in the DL state for which it was conceived, but also in the NC states. The wall features artificially introduced cracks that simulate settlement-induced damage prior to the installation of the bars. A finite element meso-model is used for the simulation of the wall tests, featuring the artificial damage and reinforcement elements. The model is used in non-linear cyclic analyses for the simulation of the experiments. Through experimental testing and numerical modelling, the efficiency of the strengthening technique is evaluated in terms of resulting shifts in wall capacity, stiffness and failure mode. Further comments are provided concerning its applicability and structural compatibility.